INTENTION TO USE MOBILE BANKING SERVICE: EXAMINING THE ROLE OF EASE OF USE, PERCEIVED USEFULNESS AND TRUST - Yonavi, Ana; Nora, Liza; Al Bakri, Salim (FEB - Universitas Lampung, 2023)
This study aims to analyze the effect of perceived ease of use, perceived usefulness, and trust on interest in using mobile banking at Bank DKI Jakarta. This study uses a quantitative approach, survey type, and causal descriptive. The population in this study were all rupiah savings customers who have mobile banking facilities registered at Bank DKI Jakarta with a sample of 160 customers using simple random sampling technique, data collection using questionnaires, and data analysis techniques using path analysis using the SmartPLS 3.2 program. . The results of this study prove that the perceived ease of use and trust has a significant effect, but the perceived usefulness does not significantly affect the interest in using mobile banking. The novelty of the concept in this study is to develop the TAM theory with the addition of a trust variable and a focus on the intention to use mobile banking, which has not been found in previous studies